2010
DOI: 10.1002/dta.159
|View full text |Cite
|
Sign up to set email alerts
|

Towards disposable sensors for drug quality control: Dextromethorphan screen‐ printed electrodes

Abstract: A simple, rapid, reliable, and reproducible method for mass production of disposable sensors using screen-printing technology is described. Homemade printing has been characterized and optimized on the basis of effects of the modifier and plasticizers. The fabricated bi-electrode potentiometric strip containing both working and reference electrode was used as dextromethorphan (DXM) sensor. The proposed sensors worked satisfactorily in the concentration range from 10⁻⁵ to 10⁻² mol L⁻¹ with detection limit reach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 26 publications
0
16
1
Order By: Relevance
“…The plain SPCEs were soaked in different DL-ion pair(s) suspensions and used in potentiometric determination of DL hydrochloride. Results obtained showed that the electrodes soaked in DL-phosphomolybdate gave the best performance indicated by the highest slope (57 ± 0.4 mV decade -1 ) which may be attributed to the difference in solubility products of these ion pairs and their extraction into the electrode bulk solution [20], (Table 1). …”
Section: Resultsmentioning
confidence: 99%
“…The plain SPCEs were soaked in different DL-ion pair(s) suspensions and used in potentiometric determination of DL hydrochloride. Results obtained showed that the electrodes soaked in DL-phosphomolybdate gave the best performance indicated by the highest slope (57 ± 0.4 mV decade -1 ) which may be attributed to the difference in solubility products of these ion pairs and their extraction into the electrode bulk solution [20], (Table 1). …”
Section: Resultsmentioning
confidence: 99%
“…1) indicated that the developed sensors can be successfully applied for the potentiometric determination of DXM in the concentration range from 10 À7 to 10 À2 mol L À1 and CWEs were the most sensitive as the measured LOD was 7.0 Â 10 À8 mol L À1 . It is noteworthy to mention that sensors based on b-CD as sensing material, showed two magnitude of sensitivity more than that based on DXM-ion pairs [29][30][31], which may be attributed to the encapsulation of DXM molecule into the CDs toroidal cavity (host-guest interaction).…”
Section: Sensor Performancesmentioning
confidence: 96%
“…DXM electrodes incorporated with different ion-association complexes of DXM with reineckate salt or phosphomolybdic acid [29], tetraphenylborate [30,31] have recently been found in literature. The cited electrode showed a useful working range from 10 À5 to 10 À2 mol L À1 with detection limit reaching 6 Â 10 À6 mol L À1 .…”
Section: Introductionmentioning
confidence: 99%
“…The FIA system was preferred, since it allowed high sampling output with a relatively short analysis time ($ 1 min). Later, the same team developed disposable DXM sensitive potentiometric sensors based on screen printed electrodes (SPEs) using home-made carbon ink utilising the same IPs [63], as mentioned above. The modified electrodes were in the form of a bi-electrode strip having both working and reference electrodes.…”
Section: Dextromethorphanmentioning
confidence: 99%